Cytotoxic Effects of Particulate Matter on Cell Growth and Metabolism of Green Fluorescent Protein-Expressing Escherichia coli - Song, Young Hoon; Heo, Hye Ryoung; Lee, Ae Sol; Kim, Chang Sup; Seo, Jeong Hyun (The Korean journal of chemical engineering, 2025)
The toxicity of sulfate (SO 4 −2 ) and ammonium (NH 4 + ), key components of fine dust, on living organisms was investigated using recombinant green fluorescent protein (GFP)-expressing Escherichia coli as a bioindicator. The effects of individual and mixed particulate matter (PM) compounds, including CuSO₄, (NH₄)₂SO₄, and NH₄Cl, were evaluated by measuring the optical density and GFP fluorescence intensity. Escherichia coli growth was inhibited by the individual compounds at specific thresholds, with CuSO₄ being most toxic at as low as 3.8 mM. Synergistic effects were observed with mixed compounds, markedly reducing growth and fluorescence even at lower concentrations. Notably, a mixture of the three at their sub-lethal individual concentrations completely halted bacterial growth after 2 h of incubation. CuSO₄ was a more potent inhibitor than (NH₄)₂SO₄ and NH₄Cl. These findings highlighted the importance of analyzing the individual and synergistic effects of PM components.